Sex‐Specific Impact of Metabolic Dysfunction‐Associated Fatty Liver Disease on Incident Cardiovascular Diseases and Mortality - Mahsa Abbaszadeh; Farhad Hosseinpanah; Maryam Tohidi; Sahar Karimpour Reyhan; Maryam Mahdavi; Majid Valizadeh (Endocrinology, Diabetes & Metabolism)
ABSTRACT Background and Aims Considering recent revisions in the nomenclature for fatty liver disease, alongside limited data on sex‐specific differences in its cardiovascular/mortality outcomes, this study aims to investigate the prevalence and impact of metabolic‐associated fatty liver disease (MAFLD) on cardiovascular disease (CVD) and mortality in men and women over a 12‐year follow‐up period. Methods In this large population‐based cohort study, 7101 individuals aged ≥ 30 were enrolled. The prevalence of MAFLD was investigated in both genders. After excluding individuals with a history of previous CVD, 6331 participants were followed up for CVD and mortality over 12 years. Steatosis was defined as fatty liver index (FLI) ≥ 60. Multivariate‐adjusted hazard ratios (HRs) were calculated for CVD and mortality. Results The prevalence of MAFLD was 43.2%, higher in men (46.5%) than women (40.6%). Men with MAFLD (47.7 ± 12.1) were younger than women (52.2 ± 11.1). In the 12‐year follow‐up of 6331 individuals, multivariable‐adjusted CVD HRs for MAFLD were 1.36 (1.10–1.67) in men and 1.48 (1.16–1.88) in women. Adjusted mortality HRs were 1.17 (0.86–1.59) and 1.38 (1.00–1.91) in men and women, respectively. Among patients with MAFLD, a subgroup with diabetes faced the highest hazard for CVD and mortality. Conclusion This study found that MAFLD is more common in men at a younger age. Despite the higher prevalence in men, women with MAFLD face a greater risk of cardiovascular events and mortality. Findings highlight the importance of gender‐specific considerations in primary prevention programmes for MAFLD‐related cardiovascular disease and mortality.